Addison’s Disease and Dilated Cardiomyopathy: A Case Report and Review of the Literature - Viktoriya Mozolevska; Anna Schwartz; David Cheung; Bilal Shaikh; Kapil M. Bhagirath; Davinder S. Jassal (Case Reports in Cardiology)
Addison’s disease is often accompanied by a number of cardiovascular manifestations. We report the case of a 30-year-old man who presented with a new onset dilated cardiomyopathy due to Addison’s disease. The clinical presentation, treatment, and outcomes of this rare hormone mediated cardiac disorder are reviewed.